ИССЛЕДОВАНИЕ МЕХАТРОННОЙ СИСТЕМЫ ДЛЯ АВТОНОМНОГО ГЕНЕРИРОВАНИЯ НАПРЯЖЕНИЯ ПЕРЕМЕННОЙ ЧАСТОТЫ ПОСТОЯННОЙ АМПЛИТУДЫ НА БАЗЕ МАГНИТОЭЛЕКТРИЧЕСКОГО ГЕНЕРАТОРА И ПОЛУПРОВОДНИКОВОГО ПРЕОБРАЗОВАТЕЛЯ - Волков, А.Г.; Зиновьев, Г.С.; Харитонов, С.А. (Інститут електродинаміки НАН України, Київ, 2012)
Static electromagnetic processes in a mechatronic system for generating autonomous voltage consisting of a synchronous generator with permanent magnet and semiconductor converter, currentinverter, or AC-DC converter, perform the role of reactive load were investigated. Ratios for calculating the basic parameters of the converter, to assess the weight and size parameters of the systemare obtained. The work is carried out under the State contract No. 13.G36.31.0010 dated as of October 22, 2010. References 3, figures 3.